PENGARUH PRENATAL YOGA DALAM MENURUNKAN KECEMASAN IBU SAAT MENGHADAPI PERSALINAN DI PMB EN KOTA BEKASI TAHUN 2022 - Yusti, Eli (Journal of Midwifery Tiara Bunda, 2022)
Background: The anxiety level of pregnant women can be lowered by non-pharmacological measures, namely prenatal yoga, prenatal yoga is easy to practice and can be demonstrated at home. Prenatal yoga is an exercise given to pregnant women and is useful for reducing anxiety and providing a sense of comfort. Purpose of the study: The purpose of the study was to determine the effect of prenatal yoga with anxiety levels in third trimester pregnant women at the PMB EN. Research Methods: In this study including the type of quantitative inferential research, this research method uses a quasi experiment design with a one group pretest posttest design. The subjects in this study were third trimester pregnant women, given a pre-test using the Hamilton Anxiety Rating Scale (HARS) questionnaire, prenatal yoga practice was performed 2 times for 4 consecutive weeks, then a post test was conducted. The research was conducted at the Ismail Medika Clinic in Depok, with 16 respondents. The data collected will be analyzed univariate and bivariate. Conclusion: There is an effect on anxiety levels when the pre test and post test are given prenatal yoga treatment with a p value = 0.000. The null hypothesis is rejected because p <0.05. It can be concluded that “Ha is accepted”, that is, there is an influence on the pre-test and post-test, so it can be concluded that there is an “Effect of Prenatal Yoga on Anxiety of Third Trimester Pregnant Women at Ismail Medika Clinic”.